The VolSatView for Satellite Monitoring and Kamchatkan Volcanoes Study - Girina O.A.; Loupian E.A.; Efremov V.Yu.; Melnikov D.V.; Manevich A.G.; Gordeev E.I.; Sorokin A.A.; Kramareva L.S.; Uvarov I.A.; Kashnitskii A.V.; Burtsev M.A. (My University, 2018)
Annually, from 3 to 6 Kamchatkan volcanoes produce eruptions, during which the explosions eject ash to 10-15 km a.s.l., and ash clouds spread thousands of kilometers from volcanoes. Ash clouds pose a serious threat to the modern jet aviation. Scientists of KVERT have conduct daily monitoring of Kamchatka volcanoes since 1993, to mitigate volcanic hazards to airline operations and population. Since 2014, satellite monitoring of volcanoes they carried out with the VolSatView (Remote monitoring of active volcanoes of Kamchatka and the Kuril Islands) (http://volcanoes.smislab.ru) IS. The system utilize all the available satellite data, weather and video observations to ensure continues monitoring and study of volcanic activity in Kamchatka. The VolSatView work with distributed information resources and computation systems. This work was supported by the Russian Science Foundation, project No. 16-17-00042.
Keywords: 20.23.25 Информационные системы с базами знаний; 38.37.25 Вулканология